2005
DOI: 10.1213/01.ane.0000149326.45137.9a
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Two Different Hydroxyethyl Starch Solutions (6% HES 130/0.4 and 200/0.5) on Blood Viscosity

Abstract: We performed the current study to investigate the influence of 2 different hydroxyethyl starch (HES) solutions, the novel medium molecular weight HES 130/0.4 (6%) and HES 200/0.5 (6%), on plasma and whole blood viscosity in vitro and ex vivo in patients with severe head injury. For the in vitro experiments, blood was incubated with increasing concentrations (0%-50% vol/vol plasma) of either 6% HES 130/0.4 or 6% HES 200/0.5 solution. Plasma viscosity and whole blood viscosity (hematocrit [Hct] 45%) at high (94.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
4
27
0
3
Order By: Relevance
“…[14][15][16][17][18][24][25][26][27][28][29] We shared the commonly held perception that both volume effect and molecule characteristics are among the most important factors in organ protection; however, the current study demonstrated that the HES molecule plays a role in hepatoprotection against reperfusion injury. The infused volume of HES solution (13 mLÁkg -1 ) adjusted to the weight of the rats was within the doses reported for volume repletion in clinical studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[14][15][16][17][18][24][25][26][27][28][29] We shared the commonly held perception that both volume effect and molecule characteristics are among the most important factors in organ protection; however, the current study demonstrated that the HES molecule plays a role in hepatoprotection against reperfusion injury. The infused volume of HES solution (13 mLÁkg -1 ) adjusted to the weight of the rats was within the doses reported for volume repletion in clinical studies.…”
Section: Discussionsupporting
confidence: 73%
“…There is evidence of a better safety profile with HES 130/04 compared with the older colloids, and it is often preferred over pure crystalloid regimens because of its prolonged intravascular half-life and positive impact on blood rheology and tissue oxygenation. [24][25][26][27][28][29] Moreover, Lang et al 18 showed a significant attenuation of inflammatory markers, such as interleukins 6 and 8 and soluble Fig. 1 Alanine aminotransferase (ALT) levels in animals that were subjected to one hour of 70% warm ischemia and two hours of reperfusion and in sham-operated controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences after hemodilution with HES 650/0.42 as compared with HES 130/0.42 have been observed by relating the decrease in hemoglobin concentration to the measured HES in vivo molecular weights ( fig. 6F) 26,27 The predominant rheologic effect of colloids consists in the reduction of whole blood viscosity proportional to the magnitude of their plasma volume expansion. 27 Plasma viscosity, however, is determined principally by the number and physical properties of dissolved macromolecules.…”
Section: Discussionmentioning
confidence: 99%
“…6F) 26,27 The predominant rheologic effect of colloids consists in the reduction of whole blood viscosity proportional to the magnitude of their plasma volume expansion. 27 Plasma viscosity, however, is determined principally by the number and physical properties of dissolved macromolecules. 27 Accordingly, progressive acute normovolemic hemodilution with HES 650/0.42 and HES 130/0.42, respectively, leads to improved rheologic conditions by demonstrating a significant decrease of whole blood viscosity (24%) as well as a strong downward trend of plasma viscosity (6%) (figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown experimentally that pulmonary capillary leakage is prevented to a greater extent by HES than by gelatin [70]. Improvement of microcirculation [71] and decrease of plasma viscosity by HES but not by gelatin [72] may also be translated into good tissue oxygenation not seen during the administration of Ringer's lactate alone [73,74] (Fig. 2).…”
Section: Colloid Choice For Hypovolemiamentioning
confidence: 85%